Fatigue strength evaluation and fracture behavior of joined dual phase steel/AA6061-T6 aluminum alloy (Fracture and Structural Integrity, 2019)
The fatigue strength evaluation and fracture behavior for a dual phase steel-AA6061-T6 bonded joints with three different adhesives (DC-80, Betamate 120 and MP55420) are presented in this paper. Single lap shear tests were used to determine maximum shear loads, for the single lap shear testing for 5.0 mm overlap length were 2 to 3.5 times higher in comparison to the 12.7 mm overlap length specimens. The results for the strain measurement revealed that higher strain-stress were developed in the 6061-T6 aluminum alloy adherend and in all cases they were lower than the adherends yield strength. Fatigue testing was carried out at 30, 50 and 70 % of the maximum shear load, 0.1 of reversibility load ratio (R) and 30 Hz of frequency. After testing, Basquin and Wholer graphs were built for each adhesive at 12.7 and 50.0 mm of overlap length. The results suggested that at higher overlapping, the cyclic maximum load increased. Additionally, the maximum fatigue loading at 10^6 cycles for MP55420 adhesive was 1.3 kN for an overlapping of 12.7 mm and 2.9 kN for 50 mm. For DC80 adhesive was 1.75 kN for overlapping 12.7 mm and 4.8 kN for 50 mm. Finally, for the Betamate 120 adhesive was 1.8 kN for 12.7 mm of overlapping and 6 kN for 50 mm. The post-fracture visual inspection revealed that MP55420 and Betamate 120 adhesives had a cohesive failure, while the DC-80 showed cohesive-adhesive failure. Additionally, the scanning electron microscopy evaluation on the spew fillet revealed resolved striations and a network of small micro-dimples for the Betamate 120 and MP55420 adhesives. On the other hand, DC-80 adhesive exhibited notable facet fragile failure that was confirmed by the shape of stress-strain plot with straight line from the origin to the point of fracture.
Keywords: Fatigue; Overlap length; Adhesive joint strength